2014
DOI: 10.1111/mmi.12674
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ordinated regulation of the extracytoplasmic stress factor, sigmaE, with other Escherichia coli sigma factors by (p)ppGpp and DksA may be achieved by specific regulation of individual holoenzymes

Abstract: Summary The E. coli alternative sigma factor, σE, transcribes genes required to maintain the cell envelope and is activated by conditions that destabilize the envelope. σE is also activated during entry into stationary phase in the absence of envelope stress by the alarmone (p)ppGpp. (p)ppGpp controls a large regulatory network, reducing expression of σ70-dependent genes required for rapid growth and activating σ70-dependent and alternative sigma factor-dependent genes required for stress survival. The DksA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 77 publications
2
36
0
Order By: Relevance
“…The structures described in this work provide straightforward models of how DksA alone and together with ppGpp block transcription initiation. However, DksA/ppGpp and TraR are also able to activate transcription at promoters such as those encoding genes for amino acid biosynthesis (Gopalkrishnan et al, 2017;Paul et al, 2005) and promoters regulated by the alternative σ E factor (Gopalkrishnan et al, 2014). Mechanisms of transcription activation via secondary channel binding proteins cannot be elucidated directly from the crystal structures determined in this study.…”
Section: Activation Of Transcription By Ppgpp and Dksamentioning
confidence: 82%
“…The structures described in this work provide straightforward models of how DksA alone and together with ppGpp block transcription initiation. However, DksA/ppGpp and TraR are also able to activate transcription at promoters such as those encoding genes for amino acid biosynthesis (Gopalkrishnan et al, 2017;Paul et al, 2005) and promoters regulated by the alternative σ E factor (Gopalkrishnan et al, 2014). Mechanisms of transcription activation via secondary channel binding proteins cannot be elucidated directly from the crystal structures determined in this study.…”
Section: Activation Of Transcription By Ppgpp and Dksamentioning
confidence: 82%
“…Full appreciation of the role of Csr in extracytoplasmic stress will require further investigation of CsrA inhibitory effects on RseA (35). Interestingly, ppGpp activates rpoE expression in the stationary phase of growth, independently of envelope stress (109), which should create additional positive feedback between the Csr and ECF systems (Fig. 5B).…”
Section: Interaction Of Csr With Other Global Regulatory Systemsmentioning
confidence: 99%
“…Nevertheless, recent reports indicated that DksA and ppGpp can have independent or opposing effects (1620) or their effects may very specifically depend on the individual promoters, holoenzymes involved or stress conditions (21). One of the examples is the bacteriophage lambda pR promoter, which was shown to be inhibited by ppGpp and stimulated by DksA (18,22).…”
Section: Introductionmentioning
confidence: 99%